The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1242/jeb.01186
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and expression of theCAPA/CAP2bgene in the tobacco hawkmoth,Manduca sexta

Abstract: SUMMARY The gene coding for cardioacceleratory peptide 2b (CAP2b; pELYAFPRV) has been isolated and sequenced from the moth Manduca sexta (GenBank accession #AY649544). Because of its significant homology to the CAPAgene in Drosophila melanogaster, this gene is called the Manduca CAPA gene. The Manduca CAPA gene is 958 nucleotides long with 29 untranslated nucleotides from the beginning of the sequence to the putative start initiation site. The CAPA gene has a single open reading frame,441 nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 32 publications
2
35
0
Order By: Relevance
“…The abdominal ganglia are most likely expressing the capa gene in addition to some neurons in the SEG. This is a similar pattern that has been described for D. melanogaster (Kean et al 2002) and in the moth M. sexta (Loi and Tublitz 2004). In mosquitoes the PVKs are involved in regulating water balance as they are in D. melanogaster (Pollock et al 2004;Ionescu and Donini 2012).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The abdominal ganglia are most likely expressing the capa gene in addition to some neurons in the SEG. This is a similar pattern that has been described for D. melanogaster (Kean et al 2002) and in the moth M. sexta (Loi and Tublitz 2004). In mosquitoes the PVKs are involved in regulating water balance as they are in D. melanogaster (Pollock et al 2004;Ionescu and Donini 2012).…”
Section: Discussionsupporting
confidence: 81%
“…A similar two gene expression pattern for PK/PBAN-like peptides has been proposed for Solenopsis sp. (Choi et al 2009), Manduca sexta (Loi and Tublitz 2004), Bombyx mori (Roller et al 2008), and Periplaneta americana (Predel and Eckert 2000;Schoofs et al 1992). A search of the Anopholes gambiae genome indicates that these same two genes putatively code for peptides in the PK/PBAN family (Riehle et al 2002) The PKs produced by capa and hugin have been confirmed by mass spectroscopy in the mosquito A. aegypti (Predel et al 2010).…”
Section: Introductionmentioning
confidence: 94%
“…This work demonstrated that the Manduca sexta neuropeptide CAP2b, a member of the capa peptide family Loi and Tublitz, 2004) ] i rise was shown to occur via phospholipase Cβ and inositol 1,4,5-trisphosphate receptor (Pollock et al, 2003), and also involves Ca 2+ release via the Golgi sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA) channel . CAP2b was also shown to stimulate Ca 2+ influx through principal cell plasma membrane Ca 2+ channels -transient receptor-like (TRPL), L-type and cyclic nucleotide-gated (CNG) channels (Fig.…”
Section: Calcium Signalling In Tubule Principal Cellsmentioning
confidence: 96%
“…6a). Mass spectra from these neurons, however, contained additional prominent peptide signals that could be assigned to the products of the capa-gene (Loi and Tublitz 2004). CAPA-peptides (periviscerokinins/CAP 2bs and a single FXPRLamide) are typical of the median neurosecretory cells in the abdominal ganglia of all insects studied so , and are usually stored in abdominal perisympathetic organs.…”
Section: Resultsmentioning
confidence: 99%
“…7 Overview of the Manduca capa prohormone processing as indicated by mass spectrometric analysis of M Lb -neurons and abdominal PSOs. Cleavage sites are represented by black or hatched bars and previously predicted products (Loi and Tublitz 2004) are represented by blue bars. All products of the capa-gene, which were identified by mass spectrometry, are labelled in green.…”
Section: Discussionmentioning
confidence: 99%